Milk Yield and Milk Compositions of Lactating Cows Fed Hay and Concentrate Supplement with/without Cottonseed Cake and/or Bole (Lake Soil) - Nega Tolla; Pravee Vijchulata; Pornsri Chairatanayuth; Suwapong Sawsdiphanich (Agriculture and Natural Resources, 2006)
A study was conducted to investigate milk yield and milk compositions of lactating Holstein Friesian cows fed native hay and a concentrate supplement with/without cottonseed cake and/or bole. Thirty two animals with 524±54 kg average body weight were blocked by their expected due dates of calving. Soon after calving each animal was assigned in a randomized complete block design to one of the four dietary treatments of concentrate alone (C) (control), 45% of the the concentrate by weight replaced with cottonseed cake (C+CSC), concentrate plus 3% bole (C+bole) and 45% of the concentrate by weight replaced with 45% CSC plus 3% bole (C+CSC+bole). Intake of hay was significantly (p<0.05) different among treatments. Supplements, total dry matter, crude protein and metabolizable energy intake were not significantly (p>0.05) different among treatment groups. Crude protein intake in treatments C, C+CSC and C+CSC+bole were 13.4, 20.6 and 11.5% higher than the estimated daily requirement respectively, while the intake of those in treatment C+bole was nearly at requirement level. Intakes of ME for treatments groups of C, C+CSC, C+bole and C+CSC+bole were 4.4, 10.3, 9.6 and 13% lower than the estimated daily requirement respectively. There were no significant (p>0.05) milk yield differences among treatments. However, animals fed the treatment diets of C+CSC, CSC+Bole and C+CSC+Bole produced 7.4, 16.3 and 18.2% higher actual milk and 14.3, 24.2 and 25.7% higher 4% fat corrected milk than the control group respectively. Milk fat content was significantly (p<0.05) different among treatments. But milk fat yield, milk protein contents and yield were not significantly (p>0.05) differed among treatments. Lower milk protein contents were observed throughout the treatment groups than expected might be due to low non structural carbohydrate contents of the diets. Supplementing a concentrated diet with 3% bole alone was found biologically and economically profitable. However, optimum levels of CSC and bole to be included in a concentrate diet have to be assessed further.